(untitled) (Scientific journal of the Fergana State University, 2025)
This scientific article is about the expression of metaphors, which are considered to be the "flowerbed of the arts" in the work "Kutadgu Bilig", which is considered to be an example of early Turkic written literature, and how they were implemented by translators. The main goal is to determine how Yusuf Hos Hajib’s unique poetic skill was evaluated through the English translations made by translators Walter May and Robert Denkoff. To achieve this goal, the metaphors identified in the original "Kutadgu Bilig" were first analyzed in comparison with their expression in the Uzbek translation and were also studied with English translations. First of all, translation studies have always shown their full potential in terms of their complexity when comparing a source created in the East with a translation into another Western language. Moreover, this complexity, when it comes to the expression of metaphors in translation, reveals the relevance and necessity of the research work even more clearly. Determining whether such complexities have been resolved by translators is one of the pressing issues identified in the article. As a result of the study, it became clear that translators used literal translation, simple expression of meaning, and in some places left the metaphor intact in metaphorical expressions. This is especially common in V. May’s poetic translation. It was found that metaphorical expressions were successfully implemented in Uzbek poetic translations and R. Denkoff’s prose translations into English.